(untitled) (Journal of Bio-Science, 2026)
Industrial effluents discharge into the rivers severely degrade water quality by introducing heavy metals, organic pollutants, and excess nutrients, leading to toxicity of aquatic life and severe health risk for humans. This research aimed to explore occupational health risks and assess the discharge of effluents from a canal connected to the Jamuna River. An in-depth interview was conducted among employees of the Jamuna Fertilizer Company Limited (JFCL) to know the occupational health condition of that industry from January to June 2023. These employees reported various health problems, including eye, respiratory, and abdominal disorders, due to poor management and a lack of awareness. The Jamuna River was negatively affected by untreated waste discharged by JFCL. Water samples were collected at the discharge points of effluents from the Jamuna fertilizer plants to investigate the river’s physicochemical parameters. The results revealed that the water quality of the Jamuna River is compromised by these discharges, posing a threat to aquatic life. The average dissolved oxygen (DO) concentration measured was 4.06 ppm, below the WHO-recommended standard of 5 ppm. Although the average pH is 8.32 and the average total dissolved solids (TDDS) content is 172.33 ppm, both of these parameters are within acceptable limits, the electrical conductivity (EC) exceeds acceptable thresholds. Furthermore, concentrations of heavy metals such as lead (Pb) and cadmium (Cd) exceeded safety thresholds, threatening aquatic organisms. Low levels of dissolved oxygen (DO) were particularly detrimental to aquatic habitats in the region. During the study, pre-monsoon water temperatures remained within acceptable limits, but they exceeded these thresholds during the monsoon season. Overall, the study revealed that the water quality of the canal, which is connected to the Jamuna River, has deteriorated significantly due to untreated discharges, affecting not only aquatic life but also the entire ecosystem and local communities. J. Bio-Sci. 34(1): 63-73, 2026